Complex molecules on surfaces: in-situ electrospray deposition and photoelectron spectroscopy - Temperton, Robert H. (2017)
Furthering our understanding of next generation hight harvesting devices has the potential to revolutionise energy storage and production. This thesis discusses the use of surface science techniques, principally soft X-ray photoelectron spectroscopies, to study two types of molecular solar cell: dye sensitised solar cells and organic photovoltaic devices. Much of this work relies on electrospray deposition, which is becoming a well established technique allowing the in-situ deposition of fragile, non-volatile molecules in high vacuum environments. This thesis explores the potential use of electrospray deposition to build model photovoltaic devices, including bi-layer and bulk heterojucntion structures, to extend the use of the technique beyond the simple "molecule on a surface" type of experiment that have previously dominated the high-vacuum electrospray deposition literature.